Associations of specific types of physical activities with 10-year risk of cardiovascular disease among adults: Data from the national health and nutrition examination survey 1999-2006 - Bingsen Huang; Qian Wang; Xin Wang; Lei Wang; Peiyao Ma; Fengling Wang; Changchun Du (Frontiers Media S.A., 2022)
BackgroundPhysical activity plays a key role in the prevention of cardiovascular disease (CVD). However, previous studies focused predominantly on the associations of the total amount of physical activity with CVD. There were few evidences on the associations of specific sport disciplines with CVD. Furthermore, little was known on the interactions between the different types of sports on CVD risk. Therefore, this study aimed to examine the independent associations of specific types of physical activities with the 10-year risk of CVD, and further evaluate the interactions between specific types of physical activities on the 10-year risk of CVD in US adults.MethodsThis study used the data of the National Health and Nutrition Examination Survey (NHANES) 1999-2006. Participants aged ≥ 30 years and with free of CVD were eligible. The physical activity questionnaire is used to collect general information on leisure-time activities in the past 30 days, including the frequency, duration, and intensity of participation in each activity. The exposures of interest included cycling, swimming, aerobics, running, American Football, basketball, and racquet sports. The Framingham risk score algorithm was used to assess 10-year CVD risk based on age, high density lipoprotein, total cholesterol, systolic blood pressure, smoking status, and diabetes. A higher total score reflects a greater risk of CVD.ResultsThis study included 10829 participants. Compared to no participation, participation in cycling (β = −0.890, 95% CI:−1.278,−0.502, P < 0.001), running (β = −1.466, 95% CI:−1.837,−1.095, P < 0.001), American Football (β = −2.934, 95% CI:−3.750,−2.119, P < 0.001), basketball (β = −1.968, 95% CI:−2.645,−1.291, P < 0.001), and aerobics (β = −0.980, 95% CI:−1.352,−0.608, P < 0.001) was associated with a lower CVD risk. Furthermore, cycling was antagonistic with basketball and racquet sports in the associations with CVD risk. An antagonistic action between swimming and aerobics was also observed. Nevertheless, running was synergistic with cycling, aerobics, and racquet sports in the associations with CVD risk.ConclusionsThere were inverse associations of specific types of physical activities with CVD risk. Furthermore, there might be synergistic and antagonistic associations of multiple types of physical activities with CVD risk.